Cholecystitis with abdominal wall biloma after percutaneous transhepatic gallbladder aspiration: A case report - Toritani, Kenichiro (Int J Surg Case Rep, 2020)
BACKGROUND: Abdominal wall biloma is an uncommon entity. We herein report an extremely rare case of cholecystitis with abdominal wall biloma after percutaneous transhepatic gallbladder aspiration (PTGBA). PRESENTATION OF CASE: A 69-year-old woman was diagnosed with acute cholecystitis, and PTGBA was performed on Day 1. PTGBA was performed a second time because of re-expansion of the gallbladder and an increased CRP level on Day 3. Computed tomography was performed on Day 9 because we suspected recurrence of cholecystitis. It revealed a well-circumscribed fluid collection between the abdominal wall or the diaphragm and the liver. Based on these intraoperative findings, we diagnosed her with cholecystitis with abdominal wall biloma. Cholecystectomy and drainage of the abdominal wall biloma were performed on Day 10. The postoperative course was uneventful, and she was discharged on Day 18. DISCUSSION: Early cholecystectomy is the gold-standard treatment for acute cholecystitis, but cholecystectomy is not performed in some cases. PTGBA is much more convenient, quicker, and less costly, but inappropriate aspiration during the second PTGBA session might have spread the infected bile to the abdominal wall through the PTGBA route. CONCLUSION: This case represents the first reported case of a biloma within the abdominal wall after PTGBA. To prevent this complication, we should aspirate gallbladder bile sufficiently during PTGBA. In addition, we should consider performing alternative therapy, such as percutaneous transhepatic gallbladder drainage or an operation, when we fail to appropriately aspirate.